Vägen ut: Om metafysisk melankoli i Lotta Lotass Den svarta solen - Ljungström, Linus (Tidskrift för litteraturvetenskap, 2020)
The way out – Metaphysical Melancholy in Lotta Lotass’ Den svarta solen Following the paratextual clues of Lotta Lotass’ conceptual ’Choose Your Own Adventure’ (anti-)novel Den svarta solen (”The black sun”, 2009) this article investigates the possible connection between melancholy as a theme and Immanuel Kant’s idealistic transcendentalism. Kant’s ”Copernican revolution” which concludes that human experience consists, not of things themselves, but of appearances shaped by the subject, suggest a claustrophobic experience in the loss of knowledgeability of the world. Using Julia Kristeva’s ideas on the melancholy, this article proposes that loss of knowledge of the world is the cause (”the black sun”) for the melancholy experience that Lotass tries to convey in the novel’s labyrinthine, descriptive representation of different rooms interconnected by arrows and numbers.